In Vivo Resistance to Ceftolozane/Tazobactam in Pseudomonas aeruginosa Arising by AmpC- and Non-AmpC-Mediated Pathways - Erik Skoglund; Henrietta Abodakpi; Rafael Rios; Lorena Diaz; Elsa De La Cadena; An Q. Dinh; Javier Ardila; William R. Miller; Jose M. Munita; Cesar A. Arias; Vincent H. Tam; Truc T. Tran (Case Reports in Infectious Diseases)
Two pairs of ceftolozane/tazobactam susceptible/resistant P. aeruginosa were isolated from 2 patients after exposure to β-lactams. The genetic basis of ceftolozane/tazobactam resistance was evaluated, and β-lactam-resistant mechanisms were assessed by phenotypic assays. Whole genome sequencing identified mutations in AmpC including the mutation (V213A) and a deletion of 7 amino acids (P210–G216) in the Ω-loop. Phenotypic assays showed that ceftolozane/tazobactam resistance in the strain with AmpCV213A variant was associated with increased β-lactamase hydrolysis activity. On the other hand, the deletion of 7 amino acids in the Ω-loop of AmpC did not display enhanced β-lactamase activity. Resistance to ceftolozane/tazobactam in P. aeruginosa is associated with changes in AmpC; however, the apparent loss of β-lactamase activity in AmpC∆7 suggests that non-AmpC mechanisms could play an important role in resistance to β-lactam/β-lactamase inhibitor combinations.